Family caregivers' experiences of involuntary psychiatric hospital admissions of their relatives--a qualitative study. - Jelena Jankovic; Ksenija Yeeles; Christina Katsakou; Tim Amos; Richard Morriss; Diana Rose; Peter Nichol; Rosemarie McCabe; Stefan Priebe (PLoS ONE, 2011)
Family caregivers of people with mental disorders are frequently involved in involuntary hospital admissions of their relatives.To explore family caregivers' experience of involuntary admission of their relative.30 in-depth interviews were conducted with family caregivers of 29 patients who had been involuntarily admitted to 12 hospitals across England. Interviews were analysed using thematic analysis.Four major themes of experiences were identified: relief and conflicting emotions in response to the relative's admission; frustration with a delay in getting help; being given the burden of care by services; and difficulties with confidentiality. Relief was a predominant emotion as a response to the relative's admission and it was accompanied by feelings of guilt and worry. Family caregivers frequently experienced difficulties in obtaining help from services prior to involuntary admission and some thought that services responded to crises rather than prevented them. Family caregivers experienced increased burden when services shifted the responsibility of caring for their mentally unwell relatives to them. Confidentiality was a delicate issue with family caregivers wanting more information and a say in decisions when they were responsible for aftercare, and being concerned about confidentiality of information they provided to services.Compulsory admission of a close relative can be a complex and stressful experience for family caregivers. In order for caregivers to be effective partners in care, a balance needs to be struck between valuing their involvement in providing care for a patient and not overburdening them.